ANALISIS PENERAPAN PERATURAN PEMERINTAH NOMOR 47 TAHUN 2012 TERHADAP TANGGUNGJAWAB SOSIAL PERUSAHAAN BUMN SEBAGAI SALAH SATU PELAKU USAHA DALAM PEREKONOMIAN - Tami Rusli (KEADILAN PROGRESIF, 2020)
Social and environmental responsibility (TJSL) is one of the limited liability companies in carrying out their role in order to contribute to the development of the national economy. Article 74 paragraph (1) of the Law on Junto PP Number 47 of 2012 stipulates that, "Companies that carry out their business activities in the fields and / or related to natural resources are required to carry out social and environmental responsibilities. The problem in this study is how the application of SOE corporate social responsibility to PT Pembangunan and Perumahan (Persero) tbk. The method in this study uses a normative and empirical juridical approach. Data sourced from secondary data and primary data. Data collection procedures with literature study and field studies and qualitative data analysis. The results showed that the application of PTPP Social and Environmental Responsibility, namely a. Make improvements to the project development site as soon as possible on final lands with diversity in plant species and conservation. b. Maintain water quality from the project area before going out into public agricultural waters so that it still meets the environmental quality standards (BML). c. Maintaining soil quality. d. Community economic empowerment through the implementation of the Partnership Program with Small Business, Winning and Cooperatives, e. Community social empowerment through the implementation of the Community Development Program, f. Concerned for environmental preservation, including land restoration post project development, g. Implementation of employee health and safety guarantees as well as efforts to improve welfare. Suggestions in this research in the form of the concept of CSR in Indonesia should be able to understand and practice the CSR aspired primarily to be placed as a means of empowering the people in the economic field by creating jobs to increase independence.